Spatio-temporal variability of surface turbulent heat flux feedback for mesoscale sea surface temperature anomaly in the global ocean - Yuan, Man; Li, Furong; Ma, Xiaohui; Yang, Peiran (Frontiers in Marine Science, 2022)
The surface turbulent heat flux feedback plays an important role in the atmosphere-ocean coupling. However, spatio-temporal variability of turbulent heat flux feedback for sea surface temperature anomaly (SSTA) at oceanic mesoscales in the global ocean remains poorly assessed. In this study, we tackle this issue using an advanced statistical model, i.e., the geographically and temporally weighted regression model. The estimated time-mean turbulent heat flux feedback for mesoscale SSTA generally ranges from 20 to 50 W/(m2K) within 60°S-60°N. It is larger in the tropics than off-tropical region and locally enhanced in the equatorial cold tongues, western boundary currents and their extensions. The spatial structure of turbulent heat flux feedback for mesoscale SSTA is primarily attributed to the nonlinearity in the Clausius–Clapeyron relation and inhomogeneity in the background wind speed, whereas adjustment of surface wind speed, air temperature or moisture to mesoscale SSTA plays an important role in the regional variability. There is an evident seasonal cycle of turbulent heat flux feedback for mesoscale SSTA in the tropics and under the northern hemisphere’s storm tracks. The former is due to the seasonally varying response of surface wind speed to mesoscale SSTA, and the latter results from the seasonality of atmospheric and oceanic background states. Our analysis reveals prominent spatio-temporal variability of turbulent heat flux feedback for mesoscale SSTA governed by complicated dynamics.